Information Economy Report 2010 - United Nations Conference on Trade; Development (United Nations, 2010)
The Information Economy Report 2010: ICT, Enterprises and Poverty Alleviation is the fifth in the flagship series published by the United Nations Conference on Trade and Development (UNCTAD). As one of few annual reports that monitor global trends related to information and communication technologies (ICTs) from a development perspective, the Report is a valuable reference source for policymakers in developing countries. In the 2010 edition, special attention is given to the potential impact of ICTs in enterprises for reducing poverty and improving livelihoods. The evidence presented in this Report suggests that more attention should be given by policymakers and other stakeholders to opportunities in this area.